Socio-economic geography of the foreign world in the coordinates of A. E. Sluka: to the 100th anniversary of the scientist – native of Belarus - Sluka, Nikolai A.; Antipova, Ekaterina A. (Journal of the Belarusian State University. Geography and Geology, 2023)
The 100th anniversary of the birth of the Soviet and Russian geographer, demogeographer, country expert, specialist in the socio-economic geography of the foreign world A. E. Sluka marks 2023 June 26. Honored professor of the Lomonosov Moscow State University, doctor of science (geography) A. E. Sluka, who was born in the city of Gorki, Mogilev region, is a prominent Russian scientist in the field of world population geography, one of the leading researchers in the socio-economic geography of Western Europe, French specialist. He made an important contribution to the development of the university scientific school of socio-economic geography, founded in the 1930s by professors N. N. Baransky and I. A. Vitver. The contribution of A. E. Sluka to the development of socio-economic geography in the main areas of his scientific interests – geographical French studies, demogeographic European studies, social geography of Greater Paris is revealed. The activity of A. E. Sluka’s students in the development of these scientific directions is comprehended.
Keywords: economic and geographical country studies; geographical French studies; demogeographic European studies; social geography of Greater Paris